Reengineering carter instrument for islamic non profit organization / Erlane K Ghani and Jamaliah Said - Ghani, Erlane K; Said, Jamaliah (Research Management Institute (RMI), 2012)
This study examines the service quality performance measurement tools introduced in the previous literature. This study, subsequently propose a new performance measurement tool engineered from the best performance measurement tool that fit into the Islamic perspective within the non-profit organisations. Using content analysis, this study assesses relative strengths and weaknesses of five performance measurement tools in order to determine which instrument would best fit in the Islamic non-profit organisation perspective. The results of the analysis show that most studies have relied on SERVQUAL. (1985). Further review shows that the potential best fit model that could adapt to Islamic non-profit organisation is Carter Instrument. This study subsequently re-engineered Carter Instrument to develop INOPERF (Islamic Non-profit Organisation PERFormance). The findings in this study provide guidelines to Islamic non-profit organisations in Malaysia to measure service quality.